Appeal against decision: The loser's appeal and the winner's of the winner:: Two new features of the CPC/2015 (Revista do Tribunal Regional Federal da 3ª Região, 2016)
The essay examines the system for challenging non-aggravable interlocutory decisions in the system of the new Brazilian Code of Civil Procedure.
Keywords: CPC 2015; interlocutory decision; interlocutory appeal; cross appeal